Poly-substance use and sexual risk behaviours: a cross-sectional comparison of adolescents in mainstream and alternative education settings - Marion Henderson; Catherine Nixon; Martin J. McKee; Denise Smith; Daniel Wight; Lawrie Elliott (BMC, 2019)
Abstract Background Surveys of young people under-represent those in alternative education settings (AES), potentially disguising health inequalities. We present the first quantitative UK evidence of health inequalities between AES and mainstream education school (MES) pupils, assessing whether observed inequalities are attributable to socioeconomic, familial, educational and peer factors. Methods Cross-sectional, self-reported data on individual- and poly-substance use (PSU: combined tobacco, alcohol and cannabis use) and sexual risk-taking from 219 pupils in AES (mean age 15.9 years) were compared with data from 4024 pupils in MES (mean age 15.5 years). Data were collected from 2008 to 2009 as part of the quasi-experimental evaluation of Healthy Respect 2 (HR2). Results AES pupils reported higher levels of substance use, including tobacco use, weekly drunkenness, using cannabis at least once a week and engaging in PSU at least once a week. AES pupils also reported higher levels of sexual health risk behaviours than their MES counterparts, including: earlier sexual activity; less protection against sexually transmitted infections (STIs); and having 3+ lifetime sexual partners. In multivariate analyses, inequalities in sexual risk-taking were fully explained after adjusting for higher deprivation, lower parental monitoring, lower parent-child connectedness, school disengagement and heightened intentions towards early parenthood among AES vs MES pupils. However, an increased risk (OR = 1.73, 95% CI 1.15, 2.60) of weekly PSU was found for AES vs MES pupils after adjusting for these factors and the influence of peer behaviours. Conclusion AES pupils are more likely to engage in health risk behaviours, including PSU and sexual risk-taking, compared with MES pupils. AES pupils are a vulnerable group who may not be easily targeted by conventional population-level public health programmes. Health promotion interventions need to be tailored and contextualised for AES pupils, in particular for sexual health and PSU. These could be included within interventions designed to promote broader outcomes such as mental wellbeing, educational engagement, raise future aspirations and promote resilience.